TID based control algorithim for robot balancing - AKPOLAT, ALPER NABİ (My University, 2023)
Balancing of Motorized Robots is achieved with a controller tuned for the system to maintain stability. Motorized robot is developed based on the principle of Inverted pendulum various controllers have been implemented and tested. Tilt based control is new control technique its application being in power systems research area. The Tilt based controllers for robotic applications might help in improving overall system performance. But Tilt based controllers are good at attaining stability within a quick period, these characteristics can be taken advantage in robotic applications. Tilted Integral Derivative (TID) and PID Controller is tuned with respect to the mathematical model. The motorized robot is modeled based on inverted pendulum principle. The system response for both controller is analyzed for change in performance, ISA, IAE, ITAE. The controller response is also visualized with a CAD model of the robot in a simulated environment to analyze the performance.
Keywords: Tıp; Sosyal ve Beşeri Bilimler; Sosyoloji; Kütüphanecilik; Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Sinyal İşleme; Bilgisayar Bilimleri; Algoritmalar; Bilgi Güvenliği ve Güvenilirliği; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyoistatistik ve Tıp Bilişimi; Mühendislik ve Teknoloji; Medicine; Social Sciences and Humanities; Sociology; Library Sciences; Information Systems, Communication and Control Engineering; Signal Processing; Computer Sciences; algorithms; Information Security and Reliability; Health Sciences; Fundamental Medical Sciences; Biostatistics and Medical Informatics; Engineering and Technology; Klinik Tıp (MED); Mühendislik, Bilişim ve Teknoloji (ENG); Sosyal Bilimler (SOC); Klinik Tıp; Bilgisayar Bilimi; Mühendislik; Sosyal Bilimler Genel; TIBBİ BİLİŞİM; BİLGİSAYAR BİLİMİ, YAPAY ZEKA; BİLGİSAYAR BİLİMİ, BİLGİ SİSTEMLERİ; TELEKOMÜNİKASYON; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; BİLGİ BİLİMİ VE KÜTÜPHANE BİLİMİ; Clinical Medicine (MED); Engineering, Computing & Technology (ENG); Social Sciences (SOC); CLINICAL MEDICINE; COMPUTER SCIENCE; ENGINEERING; SOCIAL SCIENCES, GENERAL; MEDICAL INFORMATICS; COMPUTER SCIENCE, ARTIFICIAL INTELLIGENCE; COMPUTER SCIENCE, INFORMATION SYSTEMS; TELECOMMUNICATIONS; ENGINEERING, ELECTRICAL & ELECTRONIC; INFORMATION SCIENCE & LIBRARY SCIENCE; Bilgisayar Ağları ve İletişim; Fizik Bilimleri; Bilgisayar Bilimi Uygulamaları; Bilgisayarla Görme ve Örüntü Tanıma; Bilgi sistemi; Bilgi Sistemleri ve Yönetimi; Sosyal Bilimler ve Beşeri Bilimler; Elektrik ve Elektronik Mühendisliği; Tıbbi Bilişim; Computer Networks and Communications; Physical Sciences; Computer Science Applications; Computer Vision and Pattern Recognition; Information Systems; Information Systems and Management; Social Sciences & Humanities; Electrical and Electronic Engineering; Health Informatics; Self-Balancing Robot; Tilt based controller; Tilt Integral Derivative